In vitro multiple shoot regeneration from corm bud explant in ghet kachu, typhonium trilobatum schott - a medicinal aroid (Bangladesh Journal of Scientific and Industrial Research, 2012)
An efficient in vitro regeneration protocol was developed in medicinal aroid, Ghetkachu (Typhonium trilobatum Schott) using field grown corm bud explant. Highest percentage (75 %) of direct multiple shoot regeneration obtained in MS media supplemented with 5.0 mgL-1BAP + 1.5mg L-1NAA. Callus formation occur (80 %) in MS media containing 0.5mgL-1BAP + 2.0mgL-1NAA. The appearance of calli was white, creamy white light green in colour and the texture of calli were soft, friable and semi hard and compact. Shoot regeneration (85 %) obtained from calli in MS medium having 5.0mgL-1BAP +1.0mgL-1NAA. The regenerated plantlets were successfully acclimatized with loamy fertile soil and survived cent percentage in natural condition.   DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11454   Bangladesh J. Sci. Ind. Res. 47(2), 211-216, 2012